Evil in Civilizations and Solutions - Andregg, Michael M. (Nova, 2015)
EVIL IN CIVILIZATIONS AND SOLUTIONS Michael Andregg* University of St. Thomas, St. Paul, Minnesota, USA ABSTRACT This is an attempt to analyze “evil” and search for solutions. To simplify the analysis, the phenomena that concern us are divided into three categories: individual, organizational, and the possibility of supernatural evil. Each is briefly described and exemplified. Particular attention is paid to psychopathic personalities among individuals and to secret power systems among groups; both are especially prone to evil acts. Plus, they interact synergistically. Opinions on evil from major religious traditions are compared. A small section on the evolution of evil in civilizations is followed by a section of proposed solutions to this transcendent global problem. Keywords: Evil, Organizational Evil, Civilizations, Psychopathic Personalities, Spies INTRODUCTION Human civilization is in crisis. To a degree, it always has been thus. Civilizations have risen, fallen, transformed and clashed many times. Some posit cycles of growth and decay. But today, human survival itself is at risk. That is new. Predatory leaders with “psychopathic” personalities sometimes gain control of powerful nations. Catastrophic ideologies can then arise, like “Nazi Fascism”, “Communism” or market fundamentalism (abhorrence of regulation and taxes to support common goods) that result in the violent deaths of scores of millions of people in hot and cold wars that may last for decades.
This was a third chapter I wrote for books edited by Andrew Targowski, Marek Celinsky or both. The focus on evil is rare, but that is what they asked for and I have focused in evil in civilizations, organizations, and individual people for a long time. The concept of organizational evils is particularly important and explicated. The concept of possible 'supernatural' evils (like a Devil, or Satanic force opposing a God concept) is especially difficult, but we address it as best we can. All such work (of mine) ends with possible solutions, because we have concluded this in necessary for literature on such difficult topics as 'evil.'
Keywords: Evil; organizational evil; civilizations; psychopathic personalities; spies